2020
DOI: 10.1108/meq-02-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of lifestyle on sustainable consumption behavior: a sharing economy perspective

Abstract: PurposeThe purpose of this study is to investigate the potential determinants of sustainable consumption behavior. This study describes lifestyle of health and sustainability (LOHAS) tendency and the effects of such lifestyles on the behavioral intentions for sustainable consumption in sharing economy.Design/methodology/approachThis research adapts LOHAS tendency, consumer attitude, subjective norm, perceived behavioral control and consumers' behavioral intention for sustainable consumption scale in Indian con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
74
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 72 publications
11
74
1
4
Order By: Relevance
“…Both theories posit the association between attitude and behaviour. Many studies have employed TPB to explore consumer attitude and behaviour towards green products (Gupta, 2021; Han and Kim, 2010; Matharu et al , 2020; Yadav and Pathak, 2017). On the contrary, many studies found a weak relationship between consumer attitude towards green products and purchase behaviour.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Both theories posit the association between attitude and behaviour. Many studies have employed TPB to explore consumer attitude and behaviour towards green products (Gupta, 2021; Han and Kim, 2010; Matharu et al , 2020; Yadav and Pathak, 2017). On the contrary, many studies found a weak relationship between consumer attitude towards green products and purchase behaviour.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Attitude is considered as the prominent factor affecting the green purchase behaviour of consumers (Dhir et al , 2021; Zhang and Dong, 2020). Pioneer researchers have demonstrated that consumers' attitude significantly influences environmentally concerning intentions and environmentally conscious consumer behaviour (Chaudhary and Bisai, 2018; Cherian and Jacob, 2012; Hoyer and MacInnis, 2004; Matharu et al , 2020; Mohd Suki and Mohd Suki, 2015; Roberts, 1996; Zhang and Dong, 2020). So far, two types of eco-friendly attitudes, namely, general attitude and specific attitudes, have been studied.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Over the past 30 years, many empirical studies have aimed at describing the typology of consumer attitudes to sustainable development. Typology studies differ in many respects, the consumption context (Maciejewski et al, 2020;Moschis et al, 2020;McGarry and Higgins, 2017), the sustainability focus (e.g., ethical consumption, lifestyle of health, Lin, 2020;Miczyńska-Kowalska, 2020;Matharu, Jain, and Kamboj, 2020), the dimensionality of the sustainable consumption concept (one or multiple dimensions), the focal sustainability facet (e.g., environmentally friendly consumption), the segmentation variables (e.g., attitudes, personal traits, human values), the profiling attributes (socioeconomic variables), the segmentation structure (segments reflecting either different low-to-high levels of general sustainability concern or mirroring a multifaceted consumption phenomenon) and the relationships of the segments to (actual) buying behavior (Balderjahn, et al, 2018;Anjam, et al, 2020). Finally, not at all sharing economy should be treated as a "potential new pathway to sustainability" (Heinrichs, 2013;Wang and Yu, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study revealed that multicriteria decision-making (MCDM) methods are used for analyzing the barriers, challenges, drivers, enablers, performance and practices of SSCM [23]. In addition to these aspects of the supply chain, the researchers also conducted many studies on environmental themes and intentional consumption behavior, e.g., natural airborne TiO2 [27]; ecology [28]; corporate social responsibility [29]; attitude [30]; sustainable consumption [31]; sustainable production characteristics [32]; premium price [33]; psychographic factors [34]; green brands [35]; knowledge [36]; energy efficient home appliances [37]; consumers attitude [38]; psychological climate [39]; eco-label credibility [40]; culture [41]; eco-friendly food behavior [42]; green advertising [43]; emotional factors [44]; lifestyle [45]; greenness exposure [46]. However, rare research studies are found on green supply chain management, strategic green market orientation, corporate social responsibility, green image, and green consumption intention.…”
Section: Introductionmentioning
confidence: 99%